Project – Based Learning as a strategy to improve communicative skills in English - Prieto Gómez, Ana Elizabeth (2025)
The objective of the study was to propose Project-Based Learning (PBL) strategies to strengthen the English communication skills of fifth-year Basic Education students at the private school “Sendero de Luz,” located in the city of Guayaquil, during the 20242025 school year. The present research was conducted using a quantitative, descriptive, and explanatory approach. The theoretical, empirical, and statistical methods were applied for the presentation and analysis of results. A pre-test and post test design was applied to a single experimental group, and a checklist was used to evaluate communication skills. Fluency, grammar, pronunciation, and coherence in oral production were evaluated. Descriptive statistics were used for data analysis, using frequencies and percentages to characterize student performance before and after the intervention. The results showed deficiencies in the aspects evaluated, which were related to the teaching method used in the institution, where traditional teaching prevails. With the application of PBL, positive changes were observed in learning, motivation, active participation, and collaboration among students, generating observable improvements in fluency, sentence construction, the use of auxiliary verbs, and oral interaction It was concluded that the implementation of project-based learning through role-play improves communication skills. In addition, it promotes student participation in their learning process, transforms the role of the teacher in the teaching process, motivates students to construct their own learning, and makes them feel responsible for this process. It is recommended that studies be developed that contribute to promoting the use of this methodology to improve the process of teaching and learning the English language.